Current Anti-HPA-1a Standard Antibodies React with the β3 Integrin Subunit but not with αIIbβ3 and αvβ3 Complexes - Bayat, Behnaz; Traum, Annalena; Berghöfer, Heike; Werth, Silke; Zhu, Jieging; Bein, Gregor; Sachs, Ulrich J.; Santoso, Sentot (Thrombosis and Haemostasis, 2019)
Background Fetal/neonatal alloimmune thrombocytopenia (FNAIT) results from maternal alloantibodies (abs) reacting with fetal platelets expressing paternal human platelet antigens (HPAs), mostly HPA-1a. Anti-HPA-1a abs, are the most frequent cause of severe thrombocytopenia and intracranial hemorrhage (ICH).Objectives Titration of anti-HPA-1a in maternal serum using standard National Institute for Biological Standards and Control (NIBSC) 03/152 is one diagnostic approach to predict the severity of FNAIT. Recently, we found three anti-HPA-1a subtypes reacting with the β3 subunit independently or dependently from complexes with αIIb and αv. Endothelial cell-reactive anti-αvβ3 abs were found predominantly in cases with ICH. Our aim was to assess whether available standard material represents all anti-HPA-1a subtypes.Materials and Methods In this study, anti-HPA-1a sera (NIBSC 03/152) and human monoclonal antibodies (moabs) against HPA-1a (moabs 26.4 and 813) were evaluated using transfected cell lines expressing αIIbβ3, αvβ3 or monomeric cβ3.Results Flow cytometry analyses with well-characterized murine moabs recognizing αIIbβ3, αvβ3, or β3 alone demonstrated that AP3 reacts compound-independently, whereas compound-dependent moabs Gi5 and 23C6 reacted only with complexes. NIBSC 03/152, moabs 26.4, and 813 against HPA-1a reacted like AP3, same results were obtained with monomeric cβ3 in immunoblotting. Antigen capture assay targeting endothelial cells showed anti-HPA-1a reactivity disappearance after cβ3 beads adsorption. Furthermore, in contrast to anti-HPA-1a abs from ICH cases, none of NIBSC 03/152, 26.4, and 813 inhibited tube formation.Conclusion These results suggest that current anti-HPA-1a standard material contains only the anti-β3 subtype. The absence of anti-αvβ3 makes NIBSC 03/152 less suitable as standard to predict the severity of FNAIT.
Keywords: fetal and neonatal alloimmune thrombocytopenia; antihuman platelet antigen-1a; intracranial hemorrhage; αIIbβ3; αvβ3